Pengaruh sistem informasi penilaian kinerja dan tunjangan tambahan penghasilan terhadap kinerja pegawai - Sugiani, Sugiani; Hudayah, Syarifah; gani, irwan (Faculty of Economics and Business Mulawarman University, 2018)
Performance Appraisal Information System, Supplementary Income Benefits, and Performance Employees are meruapakan one unity and mutually related to each other in the performance appraisal and compensation to the Government of Samarinda City. The application of performance appraisal and compensation information system in the form of additional income support is an effort of Samarinda City Government in an effort to give motivation to the employees to improve their performance. The purpose of this study is to determine the effect of performance appraisal information systems and additional income allowances on the performance of employees of the Department of Education Samarinda City. This research was conducted in Samarinda City Education Office. The population in this study as many as 120 employees, while the samples taken as many as 55 respondents selected simple random sampling. Validity test and test reliability of variable indicator questionnaire using SmartPLS version 3.2.6 with requirements to meet outer model, while hypothesis testing using model structure test (inner model) using SmartPLS program version 3.2.6. The result of the research indicates that the items of variable indicator have fulfilled the criteria of validity and reliability. Test the validity of loading factor, cross loading, AVE value indicates that the instrument is valid. The reliability test tested using composite realibility and Cronbach's Alpha has been eligible. Furthermore, the hypothesis test by using SmartPLS shows that the system of performance appraisal information (e-logbook) has positive and significant effect to the additional allowance of earnings, the additional allowance of earnings has positive and significant effect to the employee performance, while the performance appraisal e-logbook system has positive Not significant to employee performance. The suggestion that can be given is that the city government of Samarinda should improve the performance appraisal information system so that it can describe the performance of the employees, not just the daily activities.Keywords: performance appraisal information system, additional income supplement, employee performance